Brain-derived-neurotrophic-factor (BDNF) stress response in rats bred for learned helplessness - Vollmayr, Barbara; Faust, H.; Lewicka, Sabina; Henn, Fritz A. (Molecular psychiatry, 2001)
Stress-induced elevation of glucocorticoids is accompanied by structural changes and neuronal damage in certain brain areas. This includes reduced expression of brain-derived neurotrophic factor (BDNF) in the hippocampus which can be prevented by chronic electroconvulsive seizures and antidepressant drug treatment. In the last years we have bred two strains of rats, one which reacts with congenital helplessness to stress (cLH), and one which congenitally does not acquire helplessness when stressed (cNLH). After being selectively bred for more than 40 generations these strains have lost their behavioural plasticity including their sensitivity to antidepressant treatment. We show here that in cLH rats, acute immobilization stress does not induce a reduction of BDNF expression in the hippocampus which is observed in Sprague-Dawley and cNLH rats. All animals tested exhibited elevated corticosterone levels when stressed, an indication, that in cLH rats regulation of BDNF expression in the hippocampal formation is uncoupled from corticosterone increase induced through stress. This may explain the lack of adaptive responses in this strain.
Gesehen am 09.11.2020